Taking all the t's to one side of the equation, and the numbers to the other side:
7t - 10t + 4t = 8 + 5 ***; so that 11t - 10t = 13, or t = 13.
Check this solution back in the original equation:
7 t - 5 = 91 - 5 = 86, while 10t + 8 - 4t = 130 +8 - 52 = 138 - 52 = 86. Good!
Both sides, evaluated with t = 13, are equal, confirming that t = 13 is the solution.
*** Notice that when a "+" sign is "carried across the '=' sign,' it becomes a "-" sign. Conversely, a "-" sign carried across becomes a "+" sign. That's the key to dealing with simple equations like this. Do try it for yourself next time, and remember to check your answer, also, at the end.
Good Luck!
Live long and prosper.
2006-12-14 09:53:34
·
answer #1
·
answered by Dr Spock 6
·
0⤊
0⤋
7t - 5 = 10t + 8 - 4t
subtracting 10t from both side of the equation gives
7t - 10t - 5 = 8 - 4t
adding 4t to both sides of the equation gives
7t + 4t -10t - 5 = 8
adding 5 to both sides of the equation gives
7t + 4t - 10t = 8 + 5
adding the t's gives
1t = 8 + 5
which gives
1t = 13
But 1t is the same as writing "t" mathematically or 1 X t, therefore
t = 13
QED
2006-12-14 18:03:03
·
answer #2
·
answered by Gaz 5
·
0⤊
0⤋
7t-5=10t+8-4t?
7t - 10t + 4t = 8 + 5
t = 13
<>>
2006-12-14 18:00:35
·
answer #3
·
answered by aeiou 7
·
0⤊
0⤋
7t-5=10t+8-4t
-4t -4t
7t-5=6t+8
+5 +5
7t=6t+13
-6t -6t
t=13
2006-12-14 18:00:59
·
answer #4
·
answered by id_35x 1
·
0⤊
0⤋
7t-5=10t+8-4t First, combine all like terms.
-5-8 = -7t + 10t -4t
-13 = -t
13 = t
2006-12-14 17:56:01
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
t = 13
2006-12-14 17:53:37
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
t=13
2006-12-14 17:59:19
·
answer #7
·
answered by Naveen N 2
·
0⤊
0⤋
7t = 6t + 8 + 5
t = 13
2006-12-14 17:57:08
·
answer #8
·
answered by ships 2
·
0⤊
0⤋
if you are solving for t then here it is
7t - 5 = 6t + 8 just combine like terms
t - 5 = 8 subtract 6t from both sides
t = 13 then add 5 to both sides and you get what t is equal to
2006-12-14 17:57:07
·
answer #9
·
answered by huliagulia 1
·
0⤊
0⤋